HUBUNGAN PERMAINAN EDUKATIF DENGAN KREATIVITAS DAN BAKAT PADA ANAK AUTISME SPECTRUM DISORDER (ASD) DI SLB-C BINTORO KABUPATEN JEMBER - Suryaningsih, Yeni; Putri, Naning Anggraini; Febrianti, Tri Ucarin (Universitas Muhammadiyah Lamongan, 2021)
Introduction:Educational games are games that are able to stimulate and train children's brain development and stimulate children's creative thinking, Autism Spectrum Disorder (ASD) requires support in optimal development in creativity and talents possessed. Method:The type of research in this study is Correlation Research, while the research design is a Cross Sectional Study with a sample of 30 respondents who were taken using a total sampling technique. This research was conducted at SLB-C Bintoro Jember. in April 2021 by collecting data using a questionnaire. The analysis used in this study is the Spearman Rho test where this study determined the level of significance (α) 5% (0.05). Result: Based on data analysis, 28 respondents with a percentage of 93.3% are included in the category of optimal Educational games, 27 respondents with a percentage of 90.0% are included in the category of optimal creativity and talent. With the results of the Spearman Rho test it was found that value = 0.001 < 0.05. Discussion:This research is recommended for parents to be more supportive in creativity and talent in children with Autism Spectrum Disorder (ASD) are optimal.Keywords : Educational Games, Creativity and Talent, Autism Spectrum Disorder (ASD)